Hubungan Perilaku Asertif Perawat dengan Kualitas Pelayanan Keperawatan Rumah Sakit TK III Dr Sindhu Trisno - Mutia Ahsun Raokang; Arniawan; Elifa Ihda Rahmayanti (Universitas Widya Nusantara, 2025)
Abstract Nurses’ assertive behavior is an important aspect of nursing services because it plays a crucial role in establishing effective communication. Suboptimal assertive behavior may lead to a decline in the quality of nursing care. This study aimed to examine the relationship between nurses’ assertive behavior in providing care and the quality of nursing services at TK III Dr. Sindhu Trisno Hospital. A quantitative study with a cross-sectional design was conducted from April 17 to April 27, 2025. The study population consisted of 711 patients from the June 2024 period, with a sample of 42 respondents selected using proportionate stratified random sampling. Data were collected using questionnaires on nurses’ assertive behavior and the quality of nursing services. Data analysis included univariate and bivariate analyses using the chi-square test with a significance level of p < 0.05. The results showed that most respondents rated nurses’ assertive behavior and the quality of nursing services as good (76.2%). Bivariate analysis indicated a significant relationship between nurses’ assertive behavior and the quality of nursing services (p = 0.001). It was concluded that there is a significant relationship between nurses’ assertive behavior and the quality of nursing services at TK III Dr. Sindhu Trisno Hospital; therefore, enhancing nurses’ assertive behavior is expected to improve service quality and patient satisfaction.